Karakteristik Manuskrip Al-Qur’an Dan Pemanfaatannya Di Dusun Pallarangan Kabupaten Majene - Hikmah Amir, Nurul; Mahmud, Basri; Syarif, Syarif (Al-Bayan: Jurnal Ilmu al-Qur'an dan Hadist, 2023)
This study aims to describe manuscripts of the Qur'an in Pallarangan Hamlet, Simbang Village, Pamboang District, Majene Regency, West Sulawesi Province. This research is a qualitative research based on the results of direct observation and also interviews. There are two data sources in this study, namely primary data and secondary data. Primary data is in the form of information from manuscripts and the main resource persons, namely the caretaker of the manuscript, Mr. Abdul Haris, the Head of Simbang Village, namely Mr. Rahmadi, the Head of Pallarangan Hamlet and community leaders, while the secondary data is in the form of information that has relevance to this research. In this study, a codicology study approach was used that examined the physical condition of the manuscript and a philological study that examined rasm and qira'at. The results of this study show that information about manuscript history is only sourced from stories that have been passed down for generations. This manuscript has a function in the life of the local people, one of which is in the tradition of medicine. The manuscript also has several symbols, such as hizb markers, juz, waqaf, and nishful qur'an. In addition, it also has illumination at the beginning and end. The verse separator sign is not accompanied by a verse number. This research also reveals aspects of qira'at where it was found that this manuscript uses the qira'at of Imam 'Ashim of Hafsh. As for the aspect of writing rasm, it was found that there were some lafadz that did not conform to the Ottoman rules of rasm.